Dietary Supplementation of Dried Curry, Drumstick and Pepper Leaves on the Performance and Serum Characteristics of Broiler Chicken - Jayathilaka, B.R.; Nayananjalie, W.A.D.; Adikari, A.M.J.B.; Jayawardana, B.C.; Liyanage, Ruvini (International Journal of Livestock Research, 2018)
A study was conducted to determine the growth performances, carcass and serum characteristics of broiler chicken fed diets supplemented with curry leaves (Murraya koenigii), drumstick leaves (Moringa oleifera) and pepper leaves (Piper nigrum) powder. Experiment was conducted with day old, one hundred and sixty broiler chicks. The growth performance, carcass characteristics and serum lipid profile of broilers were evaluated. Results of the study revealed that supplementation with drumstick and pepper leaves significantly improved (P < 0.05) the body weights of broilers. Feed conversion ratio was significantly lower (P < 0.05) in drumstick and curry leaf powder supplemented birds. The carcass weight was significantly higher (P < 0.05) in the birds fed with pepper leaf powder. Pepper leaf powder significantly improved the serum HDL cholesterol level compared to the drumstick leaf powder fed chicken. The dietary supplementation of curry, drumstick and pepper leaves improve the growth performances, carcass and serum characteristics of broiler chicken.